The Effect of Nitrogen Sources on the Productivity and Biochemical Composition of Spirulina (Arthrospira) platensis - Janethida Kiatmontri; Suneerat Ruangsomboon (My University, 2023)
Assessed an appropriate nitrogen source for S. platensis culture to achieve higher biomass yields and pigments. Cultivated S. platensis in six different nitrogen sources (sodium nitrate, potassium nitrate, ammonium sulfate, urea, ammonium nitrate, and ammonium chloride). All experiments received the same concentration of nitrogen, 0.4 g nitrogen per liter. The results showed that S. platensis cultivated under sodium nitrate as a nitrogen source had the highest biomass yield (0.24 ± 0.01 g/l), protein (68.10 ± 2.92 percent), phycocyanin (198.74 ± 11.11 mg/g), and phycoerythrin (155.46 ± 9.81 mg/g). Carotenoids were also high, 0.0011 ± 0.00 mg/g which carotenoids, phycocyanin and phycoerythrin are important pigments with antioxidant activity. While S. platensis fed potassium nitrate had the highest lipid profile, 35.32 ± 7.50 percent, S. platensis treated with ammonium nitrate were high in omega-6 beneficial fatty acids. The highest was Gamma-linolenic acid (GLA) at 22.08 percent. This study demonstrates that sodium nitrate is an ideal nitrogen source for S. platensis.
Keywords: Spirulina (dietary supplement); Sodium nitrate; Potassium nitrate; Ammonium sulfate; Arthrospira; Algal biology and biofuel production